2013
DOI: 10.3109/00498254.2013.845707
|View full text |Cite
|
Sign up to set email alerts
|

In vitrometabolism of monensin A: microbial and human liver microsomes models

Abstract: 1. Monensin A, an important antibiotic ionophore that is primarily employed to treat coccidiosis, selectively complexes and transports sodium cations across lipid membranes and displays a variety of biological properties. 2. In this study, we evaluated the fungi Cunninghamella echinulata var. elegans ATCC 8688A, Cunninghamella elegans NRRL 1393 ATCC 10028B and human hepatic microsomes as CYP-P450 models to investigate the in vitro metabolism of monensin A and compare the products with the metabolites produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
2
10
0
1
Order By: Relevance
“…This is consistent with previous reports comparing xenobiotics biotransformation by Cunninghamella spp. and microsomes, which indicated that the generated metabolites are comparable . Moreover, our in silico data coincide with in vitro experiments, as three MetaSite metabolites of PZ‐1150 matched compounds identified in microsomal samples.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with previous reports comparing xenobiotics biotransformation by Cunninghamella spp. and microsomes, which indicated that the generated metabolites are comparable . Moreover, our in silico data coincide with in vitro experiments, as three MetaSite metabolites of PZ‐1150 matched compounds identified in microsomal samples.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, products 1 and 2 displayed an identical low-resolution product ion spectrum (Supplementary Materials) as well as having the same retention times as those observed in the previous studies [21, 22]. The major ion formed in the MS/MS studies results from a Grob-Wharton type fragmentation and/or H 2 O, followed by CO elimination, as previously proposed for monensin A and its metabolites (Table 1) [21, 22, 28, 29]. …”
Section: Resultssupporting
confidence: 64%
“…The analysis resulted in the [M + Na] + signal at m / z   679.4008 for product 1 (3- O -demethyl monensin A) and m / z   709,4134 for product 2 (12-hydroxy monensin A) confirming the molecular formula (mass error < 5 ppm) the same as observed for the products obtained from in vitro metabolism of monensin A by human liver microsomes and microbial transformation by fungi of Cunninghamella genus [21]. Additionally, products 1 and 2 displayed an identical low-resolution product ion spectrum (Supplementary Materials) as well as having the same retention times as those observed in the previous studies [21, 22]. The major ion formed in the MS/MS studies results from a Grob-Wharton type fragmentation and/or H 2 O, followed by CO elimination, as previously proposed for monensin A and its metabolites (Table 1) [21, 22, 28, 29].…”
Section: Resultsmentioning
confidence: 65%
“…In the case of complex biological matrices, high resolution may have an additional advantage of higher selectivity . However, when using in vitro models, the complexity of the sample is not that much of an issue and triple quadrupole or ion traps may be successfully applied …”
Section: Resultsmentioning
confidence: 99%